2006
DOI: 10.1111/j.1471-0528.2005.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and adverse pregnancy outcomes: a systematic review

Abstract: Background  Recent studies suggest that periodontal disease, as a source of subclinical and persistent infection, may induce systemic inflammatory responses that increase the risk of adverse pregnancy outcomes. Objectives  To examine the existing evidence on the relationship between periodontal disease and adverse pregnancy outcomes. Search strategy  Published studies identified via searches of the MEDLINE, EMBASE, CINAHL, and Current Contents full‐text databases. Selection criteria  We identified and selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
423
2
29

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(470 citation statements)
references
References 53 publications
16
423
2
29
Order By: Relevance
“…Potential determinants among the latter include infections (urinary, gynecological 6 , and even periodontal 21 ), capable of producing systemic inflammatory reactions. Another potential cause of preterm delivery is emotional stress, which manifests itself especially among ethnic/racial minorities 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Potential determinants among the latter include infections (urinary, gynecological 6 , and even periodontal 21 ), capable of producing systemic inflammatory reactions. Another potential cause of preterm delivery is emotional stress, which manifests itself especially among ethnic/racial minorities 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Most infectious events associated with stillbirth are acute and hence unlikely to recur, but empirically it is important to exclude chronic infectious conditions such as toxoplasmosis, syphilis and possibly Chlamydia. 20 There is some evidence that chronic periodontal disease increases the risk of adverse pregnancy outcomes, 21 and evidence from animal models suggests that these effects could include stillbirth. 22 If there is any history suggestive of periodontal disease (typically bleeding from the gums with vigorous tooth brushing) then examination and management by a dentist is prudent.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the association is variable, but two recent systematic reviews have suggested that periodontal disease is a risk for coronary heart disease and an adverse pregnancy outcome. 1,2 If periodontal disease is a signifi cant risk factor for a variety of systemic conditions, it does raise the important question of whether failure to address poor oral health increases the risk of patients succumbing to the various conditions outlined in Table 1 and their sequelae. The converse argument can also apply -that is, what impact does improving oral health have on general health?…”
Section: Introductionmentioning
confidence: 99%